Relation between gestational weight gain and pregnancy outcomes. Issue 4 (15th January 2014) - Sunsaneevithayakul, Prasert; Titapant, Vitaya; Ruangvutilert, Pornpimol; Sutantawibul, Anuwat; Phatihattakorn, Chayawat; Wataganara, Tuangsit; Talungchit, Pattarawalai
Abstract Aim The aim of this study was to evaluate the effects of gestational weight gain on pregnancy outcomes in pregnant Thai women with different pre‐pregnancy body mass indexes (BMI). Materials and Methods A retrospective study was carried out by reviewing 5200 medical records of pregnant women who delivered at the Department of Obstetrics and Gynecology, Faculty of Medicine Siriraj Hospital during 1 September 2011–1 August 2012. Inclusion criteria were singleton pregnancy with available pre‐pregnant weight and maternal height. Pre‐pregnancy BMI were categorized according to World Health Organization criteria. Pregnancy outcomes of interest were appropriate‐for‐gestational‐age infants. The optimal gestational weight gain for each BMI group was proposed to achieve a high proportion of appropriate‐for‐gestational age infants. Results Patients were divided into four groups according to their pre‐pregnancy BMI: underweight (21.3%), normal weight (64.1%), overweight (11.5%), and obese (3.1%). Optimal gestational weight gain ranges for each group were 10–18, 8–16, 6–14 and 4–8 kg, respectively. Our proposed criteria seem to be realistic, with 60% of pregnant Thai women able to adhere to the recommendation, compared to 40.5% adherence to the 2009 Institute of Medicine recommendation. There were no significant complications when following either of the recommendations. Adverse pregnancy outcomes, including large for gestational age, cesarean section, and severe pre‐eclampsia, were significantly decreased in women who complied with our recommendation. Conclusion To achieve a high proportion of appropriate‐for‐gestational‐age infants, Thai pregnant women could follow our gestational weight gain recommendation.